Patients with oral anticoagulation - Koscielny, J.; Ziemer, S.; Heymann, von C. (Hämostaseologie, 2009)
Oral anticoagulation with a vitamin K-antagonist requires special consideration when surgery or interventional procedures are planned. This is mainly due to the half life of vitamin K-antagonists and to the need for safe and effective anticoagulation prior to and during surgery as well as in the postoperative period. So far, the continuous infusion of unfractionated heparin (UFH) has been the medication of choice to ,,bridge“ patients to surgery.The use of low molecular weight heparins (LMWH) has been prospectively investigated in this setting and represents a safe alternative. The advantages of LMWH are the better dose-response relationship and reduced need for monitoring. This facilitates the bridging procedure to be started out of hospital, which may reduce hospital stay and associated costs. Furthermore, the so-called bridging of patients with oral anticoagulation prior to and during surgery reduces bleeding complications and maintains a safe anticoagulation for patients at risk.
Keywords: Oral anticoagulation; vitamin K-antagonist; perioperative bridging; unfractionated heparin; low molecular weight heparin